Flipped Classroom For Tarakanita Secretarial School - Gabriella Novianty Soedjarwo (Universitas Tarakanita, 2020)
In academic year 2019/2020, most students at Tarakanita 19-20 years old. They have been familiar with gadget and other advance of technology and internet. The idea of flipped classroom is one of the options to make use of their familiarity with internet and other technology in learning. Since they have a short span of focus, lecturers need to make use of classroom meeting to see how much students make progress. With the implementation of flipped classroom, it is expected that students can prepare themselves before class and get ready to show how much they understand about the materials in a classroom meeting. Lecturers need to facilitate students with meaningful and attractive materials, and to give meaningful feedbacks. This study aims to provide an analysis based on a number if theories about flipped classroom and Tarakanita curriculum to examine the possible application of flipped classroom at Tarakanita by considering the school curriculum, the vocational school’s objectives and flipped classroom theories. This study also intends to see the possibilities of STARKI applying flipped classroom for other courses and what are the challenges and obstacles in the application pf flipped classroom at STARKI.